Psychosocial Development of School-Age Children - Dona Yanuar Agus Santoso; Esti Mediastini; Livana PH; Yazid Basthomi (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Developmental tasks, should be accomplished by school-age children in order to achieve proper development and growth. When obstacles arise, are possibly sum up in disruption in achieving the next stage of school-age children development and growth. This study aims to determine the description of the psychosocial development of school age children in Bandengan, Kendal City. This research has been carried out through quantitative research with descriptive research design. The sample of this study was 72 school-aged children in Bandengan Kendal City who selected by purposive sampling technique. The psychosocial development questionnaire consists of 8 items regarding the characteristics of normal school children psychosocial development as the basis for the questionnaire. This questionnaire has been declared valid and reliable. The data were analyzed univariately using a frequency distribution. The results of this study indicate that the majority of school age children psychosocial development is in the abnormal category (54%), so that intervention is needed to overcome this problem. In conclusion, the school-age children are likely to have an abnormal psychosocial development, especially the younger school-age children.